Age-related change in skeletal muscle strength, size, and adiposity over 18 years in Caribbean men - Lauren S. Roe; Ryan K. Cvejkus; Victor W. Wheeler; Christopher L. Gordon; Tanya S. Kenkre; Joseph M. Zmuda; Iva Miljkovic (GeroScience, 2025)
Declines in muscle strength outpace declines in muscle mass with age, so factors like muscle adiposity (i.e., myosteatosis) may contribute to strength loss. We describe intermuscular adipose tissue (IMAT) and grip strength over 18 years among middle-aged and older African Caribbean men. We hypothesized that increases in IMAT precede the loss of muscle area and strength, and that increased IMAT is independently associated with strength decline. Men ( n = 339, 51.2 ± 5.5 years) were followed for 18.2 ± 0.9 years. Peripheral quantitative computed tomography at the calf determined IMAT (cm 2 ) and muscle area (cm 2 ) at baseline, follow-up visit 1 (FV1; 6.2 ± 0.4 years after baseline), and FV2 (12.0 ± 0.8 years after FV1). Grip strength (kg) was measured by handheld dynamometry at all visits. Generalized estimating equations determined associations between changes in IMAT and muscle area with time-varying grip strength. Grip strength decreased (mean ± SD, baseline: 51.33 ± 8.79, FV1: 47.02 ± 8.67, FV2: 40.12 ± 8.57), IMAT increased (median [quartile 1, quartile 3], baseline: 1.36 [0.73, 2.53], FV1: 1.74 [0.92, 3.14], FV2: 3.49 [2.06, 5.49]), and muscle area increased then decreased (baseline: 79.88 ± 12.33, FV1: 81.12 ± 13.88, FV2: 78.35 ± 12.72; all p < 0.05). A 1-cm 2 increase in IMAT from baseline to FV1 or FV2 was significantly associated with 0.18 kg (95% CI: −0.31, −0.06) decreased grip strength, independent of muscle area. The change in muscle area was not associated with grip strength declines ( β = 0.03, 95% CI: −0.03, 0.10). Despite initial muscle area increases, grip strength continuously decreased, and IMAT increased. Age-related increases in IMAT may contribute to the disconnect between declines in muscle strength and size. Graphical Abstract